Purists, Partisans, and the Aesthetic Dimension of Sport - Charles Robinson (Karolinum Press, 2014)
Purists, Partisans, and the Aesthetic Dimension of Sport Stephen Mumford, in his book Watching Sport, identifies two types of sports spectator - partisans and purists. Partisans are more concerned to see their team win, whether they do so in an aesthetically pleasing way or not, while purists have no such irrational commitment, and instead pursues the higher aesthetic experience of sport. The purist, Mumford argues, is superior because she watches sport for aesthetic and intellectual reasons and sees the game, it seems, more objectively, whereas the partisan is emotional and victoryseeking, experiencing the game through the lens of their desire for victory. But this distinction, I argue, doesn't do justice to the actual experience of spectators. Whilst Mumford is correct to suggest that the aesthetic dimension is vital in our enjoyment of sport, there is no reason to suppose that the partisan cannot partake in the aesthetic appreciation of sport. Furthermore, whilst winning is obviously hugely important in judging the quality of sports teams, they are likely to be more fondly regarded if they do so through the demonstration of virtues that are aesthetic in nature. Even the most vociferous of partisans are capable of appreciating such teams. Puristé, partyzáni a estetická dimenze sportu Ve své knize Watching Sport Stephen Mumford identifikuje dva typy sportovních diváků - partyzány a puristy. Partyzáni se zajímají spíše o výhru svého týmu, ať už je jejich hra estetická, nebo ne, zatímco puristé nemají tento iracionální zájem a zajímá je vyšší estetický sportovní zážitek. Mumford považuje puristy za nadřazenější, protože sledují sport z estetických a intelektuálních důvodů, a zdá se, že vidí hru objektivněji, zatímco partyzáni jsou emocionální a sledují hru skrze touhu po vítězství. Moje argumenty ukazují, že toto pojetí adekvátně nepopisuje zážitek diváků. Zatímco Mumford vhodně uvádí, že estetická dimenze sportu je důležitá pro naše potěšení ze sportu, není důvod předpokládat, že partyzáni nemohou oceňovat sport esteticky. Navíc zatímco je výhra očividně velmi důležitá při hodnocení kvality sportovních týmů, budeme je hodnotit lépe, dosáhnou-li ji prokázáním estetických hodnot. I ten nejhlučnější partyzán je schopen takové týmy ocenit.